THE EFFECT OF TASK_BASED LANGUAGE TEACHING ON STUDENTS’ READING COMPREHENSION OF TENTH GRADE OF SMK PUTRA ANDA BINJAI STUDENTS IN ACADEMIC 2018/2019 - juliantina - sebayang (Serunai : Jurnal Ilmiah Ilmu Pendidikan, 2019)
This study deals with the effect of applying task based language teaching on the students’ reading comprehension. The population of this research was the tenth grade students of SMK Putra Anda Binjai. The sample of research were two classes which were chosen  by random sampling. Twenty eight students were taken as the samples in each class. The experimental group was taught by using task based language teaching, while the control class was taught without using task based language teaching. The data were analyzed by using t-test. The calculation shows that t-observed (2.49) was higher than t-table (1.67) at the level of significance (α) 0.05 with the degree of freedom (df) 54. The result is hypothesis stated that there is significantly effect of applying task based language teaching on the tenth grade students’ reading comprehension is accepted.Key words: Task based language teaching, reading comprehension.